Antibacterial Potential of Dewandaru Leaves (Eugenia uniflora L.) Against Escherichia coli: In Vitro Study - Setiyanto, Riyan; Annisa Diyan Meitasari; Sinta Cantika Natasya; Dewi Weni Sari (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Escherichia coli is a pathogenic Gram-negative bacteria that commonly causes digestive tract infections, including diarrhea. Continuous use of antibiotics has led to an increase in bacterial resistance. Dewandaru leaves (Eugenia uniflora L.) have been known to have antibacterial activity against several pathogenic bacteria. This study aims to evaluate the antibacterial activity of dewandaru leaf extract against E. coli in vitro. Methods: Dewandaru leaves were extracted using the maceration method with 96% ethanol. The antibacterial activity test was carried out using the Kirby-Bauer disk diffusion method with gentamicin as a positive control and sterile NaCl as a negative control. The diameter of the inhibition zone was measured and analyzed statistically. Results: Dewandaru leaf extract shows antibacterial activity against E. coli with a significant zone of inhibition. An extract concentration of 80% showed moderate antibacterial activity, while concentrations of 40% and 60% did not show antibacterial activity. Conclusion: Dewandaru leaves have the potential to be a natural antibacterial agent against E. coli. Further studies are needed to isolate and identify the active compounds and evaluate the effectiveness and safety of dewandaru leaf extract in vivo.